2015
DOI: 10.1123/jsm.2013-0306
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Behavioral Loyalty through Community: Why Other Fans Are More Important Than Our Own Intentions, Our Satisfaction, and the Team Itself

Abstract: A consumer's loyalty to a specific sport team is longitudinal in nature. This longitudinal study examines the effects of consumers' attitudinal constructs (team identification, associated attachment points, consumer satisfaction, and behavioral intentions) on behavioral loyalty in the context of a professional soccer event. To test the proposed relationships, the authors assess the impact of consumers' self-reported measures (Time 1) on actual attendance frequency in the first half (Time 2) and the second half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
2
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 57 publications
9
112
2
18
Order By: Relevance
“…Empirical studies have revealed several positive aspects of brand communities including increases in brand involvement, brand loyalty, positive word-of-mouth behaviour and customer support to community members (Bagozzi & Dholakia, 2006;Muniz & O'Guinn, 2001). Also in the sport setting, managers increasingly recognize the crucial role of brand communities for key aspects such as team identity (Yoshida, Heere, & Gordon, 2015) and game attendance (Katz & Heere, 2014). Pongsakornrungsilp and Schroeder (2011) further reveal that community members play an active role in building stronger relationships with the club online.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Empirical studies have revealed several positive aspects of brand communities including increases in brand involvement, brand loyalty, positive word-of-mouth behaviour and customer support to community members (Bagozzi & Dholakia, 2006;Muniz & O'Guinn, 2001). Also in the sport setting, managers increasingly recognize the crucial role of brand communities for key aspects such as team identity (Yoshida, Heere, & Gordon, 2015) and game attendance (Katz & Heere, 2014). Pongsakornrungsilp and Schroeder (2011) further reveal that community members play an active role in building stronger relationships with the club online.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Researchers have studied factors that affect purchasing behavior of sports fans [48,58,63], including psychometric properties and fan motivation. A few studies also build predictive models of fan loyalty [4,72]. Bee and Havitz [4] suggest that fan attraction, involvement, psychological commitment, and resistance can be predictors of fan behavioral loyalty.…”
Section: Sports Fan Behaviormentioning
confidence: 99%
“…Dolton and MacKerron [11] estimate that the happiness that fans feel when their team wins is outweighted by the sadness that strikes when their team loses by a factor or two. Yoshida et al [72] build regression models based on attitudinal processes to predict behavioral loyalty. The potential influence of mobile technology on sports spectators is also examined from different angles [23,34,57].…”
Section: Sports Fan Behaviormentioning
confidence: 99%
See 2 more Smart Citations